Simplifying
x + 6 = 3x + -14
Reorder the terms:
6 + x = 3x + -14
Reorder the terms:
6 + x = -14 + 3x
Solving
6 + x = -14 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
6 + x + -3x = -14 + 3x + -3x
Combine like terms: x + -3x = -2x
6 + -2x = -14 + 3x + -3x
Combine like terms: 3x + -3x = 0
6 + -2x = -14 + 0
6 + -2x = -14
Add '-6' to each side of the equation.
6 + -6 + -2x = -14 + -6
Combine like terms: 6 + -6 = 0
0 + -2x = -14 + -6
-2x = -14 + -6
Combine like terms: -14 + -6 = -20
-2x = -20
Divide each side by '-2'.
x = 10
Simplifying
x = 10
Answer:
$200
Step-by-step explanation:
First, find the unit rate:
12/3= 4
Then multiply:
4*50= 200
Hope this helps!
Awnser:
9,12,18
Step-by-step explanation:
you have to add the smallest numbers together and it has to be greater that the greatest number.
9+12= 21
21>18
Area = Length x Width
63 = 9 x width
Width= 63 ÷ 9 = 7 feet
Answer: 7 feet